Using simulation to incorporate dynamic criteria into multiple criteria decision making - Aickelin, Uwe; Reps, Jenna M.; Siebers, Peer-Olaf; Li, Peng (Palgrave Macmillan, 2018)
In this paper we present a case study demonstrating how dynamic and uncertain criteria can be incorporated into a multi-criteria analysis with the help of discrete event simulation. The simulation guided multi-criteria analysis can include both monetary and nonmonetary criteria that are static or dynamic, whereas standard multi-criteria analysis only deals with static criteria and cost benefit analysis only deals with static monetary criteria. The dynamic and uncertain criteria are incorporated by using simulation to explore how the decision options perform. The results of the simulation are then fed into the multi-criteria analysis. By enabling the incorporation of dynamic and uncertain criteria, the dynamic multiple criteria analysis was able to take a unique perspective of the problem. The highest ranked option returned by the dynamic multi-criteria analysis differed from the other decision aid techniques. The results suggest that dynamic multiple criteria analysis may be highly suitable for decisions that require long term evaluation, as this is often when uncertainty is introduced.